Routine Molecular Screening of Patients with Advanced Non-SmallCell Lung Cancer in Circulating Cell-Free DNA at Diagnosis and During Progression Using OncoBEAM(TM)EGFR V2 and NGS Technologies - Garcia, Jessica (Mol Diagn Ther, 2021)
BACKGROUND AND OBJECTIVES: The use of ultra-sensitive diagnostic tests to detect clinically actionable somatic alterations within the gene encoding the epidermal growth factor receptor (EGFR) within circulating cell-free DNA is an important first step in determining the eligibility of patients with non-small cell lung cancer to receive tyrosine kinase inhibitors. METHODS: We present the clinical validation (accuracy, sensitivity, and specificity) of a highly sensitive OncoBEAM(TM) EGFR V2 test, which we compare to a custom next-generation sequencing assay, for the treatment of patients with non-small cell lung cancer with EGFR tyrosine kinase inhibitor therapies. The OncoBEAM(TM) digital-polymerase chain reaction method detects 36 different EGFR alterations in circulating cell-free DNA, whereas the next-generation sequencing assay covers major solid tumor oncodrivers. Of the 540 samples analyzed with the OncoBEAM(TM) EGFR V2 test, 42.4% of patients had undergone molecular testing at diagnosis (N = 229/540) and 57.7% of patients during disease progression (N = 311/540). RESULTS: The sensitivity and specificity were measured for this BEAMing assay. The number of mutant beads and mutant allelic fraction were measured for each EGFR alteration and the level of detection was established at 0.1% for a median of 2861 genome equivalent (GE) in each reaction using HD780 horizon control DNA, as well as by an internal quality reference standard. Approximately 10%, 27%, and 63% of the 540 samples contained < 1500 GE, a range of 1500–3000 GE, and > 3000 GE, which corresponded to a maximal assay sensitivity of 2.0%, 0.5–0.1%, and 0.1–0.05% mutant allelic fraction, respectively. In a routine hospital setting, 11.4% of non-small cell lung cancer tumors were positive at diagnosis for EGFR alterations, while 43.7% samples harbored EGFR mutations at progression, among which 40.3% expressed EGFR resistance mutations after first-line tyrosine kinase inhibitor treatment with first- and second-generation drugs. CONCLUSIONS: The OncoBEAM(TM) EGFR V2 is a sensitive, robust, and accurate assay that delivers reproducible results. Next-generation sequencing and BEAMing technologies act complementarily in the routine molecular screening. We show that using a next-generation sequencing assay, despite its lower sensitivity, enables the identification of rare EGFR alterations or resistance mechanisms (mutation, deletion, insertion, and copy number variation) to orient first- and second-line treatments. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s40291-021-00515-9.